2013
DOI: 10.2215/cjn.04310413
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylation of Serum Albumin and Erythropoietin Resistance in End Stage Kidney Disease

Abstract: SummaryBackground and objectives The mechanisms underlying erythropoietin resistance are not fully understood. Carbamylation is a post-translational protein modification that can alter the function of proteins, such as erythropoietin. The hypothesis of this study is that carbamylation burden is independently associated with erythropoietin resistance.Design, setting, participants, & measurements In a nonconcurrent prospective cohort study of incident hemodialysis patients in the United States, carbamylated albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
(70 reference statements)
2
32
0
4
Order By: Relevance
“…The intensity of this reaction is particularly amplified during chronic kidney disease (CKD) because of hyperuremia (25,26). High concentrations of carbamylated plasma proteins constitute a significant risk factor for cardiovascular events and mortality in hemodialysis patients (26,27). Recently, our laboratory has evidenced in a mouse model that tissue proteins, including skin collagen, were more intensely carbamylated during CKD and accumulated in the organism (28).…”
Section: Significancementioning
confidence: 99%
“…The intensity of this reaction is particularly amplified during chronic kidney disease (CKD) because of hyperuremia (25,26). High concentrations of carbamylated plasma proteins constitute a significant risk factor for cardiovascular events and mortality in hemodialysis patients (26,27). Recently, our laboratory has evidenced in a mouse model that tissue proteins, including skin collagen, were more intensely carbamylated during CKD and accumulated in the organism (28).…”
Section: Significancementioning
confidence: 99%
“…• In terms of anaemia of CKD, as mentioned above carbamylation has been linked with altered erythropoietin function [84]; a prospective cohort study of 158 haemodialysis patients found that levels of carbamylated serum albumin predicted resistance to erythropoiesis-stimulating agents and higher mortality risk [96].…”
Section: Sh Amino Acid Protein Lysylmentioning
confidence: 99%
“…12 Carbamylation was recently described as a factor inducing resistance to rhEpo treatment. 13 We, therefore, assessed albumin carbamylation as a marker for total carbamylation. As expected, the percentage of carbamylated albumin (c-alb) was higher in patients with CKD than in controls (4.4%; interquartile range, 3.6%-6.1% versus 8%; interquartile range, 6.4%-10.5%; P,0.01).…”
mentioning
confidence: 99%